Absorption and fluorescence properties of chromophoric dissolved organic matter of the eastern Bering Sea in the summer with special reference to the influence of a cold pool - D'sa, E. J.; Goes, J. I.; Gomes, H.; Mouw, C. (Digital Commons @ Michigan Tech, 2014)
The absorption and fluorescence properties of chromophoric dissolved organic matter (CDOM) are reported for the inner shelf, slope waters and outer shelf regions of the eastern Bering Sea during the summer of 2008, when a warm, thermally stratified surface mixed layer lay over a cold pool ( < 2 °C) that occupied the entire middle shelf. CDOM absorption at 355 nm (ag355) and its spectral slope (S) in conjunction with excitation-emission matrix (EEM) fluorescence and parallel factor analysis (PARAFAC) revealed large variability in the characteristics of CDOM in different regions of the Bering Sea. PARAFAC analysis aided in the identification of three humic-like (components one, two and five) and two protein-like (a tyrosine-like component three, and a tryptophan-like component four) components. In the extensive shelf region, average absorption coefficients at 355 nm (ag355, mg-1) and DOC concentrations (μM) were highest in the inner shelf (0.342 ± 0.11 mg-1, 92.67 ± 14.60 μM) and lower in the middle (0.226 ± 0.05 mg-1, 78.38 ± 10.64 μM) and outer (0.185 ± 0.05 mg-1, 79.24 ± 18.01 μM) shelves, respectively. DOC concentrations, however were not significantly different, suggesting CDOM sources and sinks to be uncoupled from DOC. Mean spectral slopes S were elevated in the middle shelf (24.38 ± 2.25 μmg-1) especially in the surface waters (26.87 ± 2.39 μmg-1) indicating high rates of photodegradation in the highly stratified surface mixed layer, which intensified northwards in the northern middle shelf likely contributing to greater light penetration and to phytoplankton blooms at deeper depths. The fluorescent humic-like components one, two, and five were most elevated in the inner shelf most likely from riverine inputs. Along the productive "green belt" in the outer shelf/slope region, absorption and fluorescence properties indicated the presence of fresh and degraded autochthonous DOM. Near the Unimak Pass region of the Aleutian Islands, low DOC and ag355 (mean 66.99 ± 7.94 μM; 0.182 ± 0.05 mg-1) and a high S ...